Analysis of Higher Order Thinking Skills in a TPACK Based Flipped Classroom Supported by Dynamic Assessment - Ahmad Zaeni; Kartono; Mulyono; Y.L. Sukestiarno (Hipotenusa: Journal of Mathematical Society, 2025)
This study aims to identify students’ mathematical higher order thinking skills (HOTS) through the implementation of a Flipped Classroom model grounded in the Technological Pedagogical and Content Knowledge (TPACK) framework and supported by dynamic assessment. A mixed method approach with a concurrent embedded design was employed. The study involved 32 prospective mathematics teachers, divided evenly into an experimental group (n = 16) receiving TPACK based Flipped Classroom instruction with dynamic assessment and a control group (n = 16) receiving conventional instruction. HOTS were measured using a validated essay based test aligned with indicators of interpretation, analysis, evaluation, inference, and problem solving. For the qualitative phase, three students representing high, medium, and low prior ability levels were purposively selected. Data were analyzed using both quantitative and qualitative techniques. Quantitative data were analyzed using paired and independent samples t-tests and N-Gain, while qualitative data were examined using open coding and thematic analysis. Descriptive results showed higher posttest scores for the experimental group (M = 74.3, SD = 10.4) compared to the control group (M = 55.1, SD = 9.0). The independent samples t-test indicated a statistically significant difference between groups (p < .05), with a large effect size (Cohen’s d = 1.65) and a moderate N-Gain of 0.58 in the experimental group. Qualitative findings revealed that the high ability student demonstrated complete alignment with HOTS indicators through coherent modeling and proof strategies, while the medium ability student exhibited accurate procedural reasoning and partial conceptual explanation. The low ability student showed limited abstraction but demonstrated incremental improvement through scaffolded feedback. The combined findings show that integrating TPACK based Flipped Classroom instruction with dynamic assessment supports deeper mathematical reasoning by linking pre class technological engagement with in class mediated learning. This study contributes to the literature by demonstrating how dynamic assessment operationalized within a TPACK aligned flipped environment can strengthen students’ HOTS across varying ability levels.